The Impact of Paradoxical Leadership on Employee Voice Behavior: A Moderated Mediation Model - Li, Xiyuan; Xue, Ying; Liang, Hao; Yan, Dong (Frontiers in Psychology, 2020)
Paradoxical leadership is associated with positive behavioral outcomes. However, the link between paradoxical leadership and voice behavior is not comprehensively studied in extant literature. This paper builds a theoretical model to reveal how paradoxical leadership facilitates promotive and prohibitive voice behavior of employees, drawing upon social cognitive theory and regulatory focus theory. We proposed a moderated mediation model that employees' voice behavior is related to paradoxical leadership through self-efficacy and psychological safety. With data 268 leader-employee pairs of questionnaires, this study conducted a structural equation model to test the conceptual framework. The results show that: (a) leader’s paradoxical leadership related to employee’s promotive and prohibitive voice behaviors positively; (b) employee’s self-efficacy and psychological safety mediate the extent of effect the superior’s paradoxical leadership has on subordinate’s voice behavior; (c) the more obvious the subordinate’s promotion focus orientation, the stronger the mediating effect of self-efficacy; (d) the more obvious the subordinate’s prevention focus orientation, the weaker the mediating effect of psychological safety. These conclusions reveal the influencing mechanism of a superior’s paradoxical leadership on a subordinate’s voice behavior. It expands paradoxical leadership-related studies, enriches studies related to the field of “leader-employee voice behavior,” and highlights the relationship between the duality of paradoxical leadership behavior on employees with different regulatory focus orientation with a new perspective.